KAJIAN RENCANA TINDAK PENATAAN RUANG TERBUKA HIJAU (RTH) DI KABUPATEN TEMANGGUNG - Eva Artmey Mangedaby; Annica Etenia (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This article provides a critical review of the planning process used in the Action Plan for arranging Green Open Space (GOS/RTH) in Temanggung Regency. The study aims to (1) map the theoretical stages of strategic planning, (2) compare those stages with practices applied in the project, and (3) derive recommendations for improving future action plans. A qualitative-descriptive approach is combined with spatial analysis, document review, projection analysis, and a SWOT-based appraisal of internal and external conditions. The review indicates that the plan follows the sequence of vision–mission formulation, environmental assessment, issue identification, and strategy design, yet key steps are simplified, especially SWOT scoring and community participation. The resulting strategy focuses on a limited set of priority parks and is not fully anchored to zoning directions in the detailed spatial plan. Strengthening analytic rigor, transparently prioritizing locations, and integrating stakeholder input are recommended to make implementation more realistic and accountable and measurable outcomes for local government.